Exploring the Effectiveness of Advergame: The Role of Transportation on Continuous Intention to Play Advergames. (July 2022) - Kim, Yunju; Lee, Heejun
This study argues that research on advergames needs to better address the relationships between players' psychological characteristics and their behavioural responses. In this article, we present a theoretical model that explains the antecedents and consequences of players' transportation experience to have positive advergame outcomes. Our model demonstrates that three key psychological traits (sensation seeking, transportability and perceived interactivity) foster positive attitudes towards the featured brand in an advergame and intention to replay the game. The results also reveal that transportability is the most influential factor than others. Then, we show a mediation effect of transportation in the association between the psychological traits and desired advergame outcomes. Implications for research and practice are discussed.